2023
DOI: 10.3390/antibiotics12061046
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio Phage VMJ710 Can Prevent and Treat Disease Caused by Pathogenic MDR V. cholerae O1 in an Infant Mouse Model

Abstract: Cholera, a disease of antiquity, is still festering in developing countries that lack safe drinking water and sewage disposal. Vibrio cholerae, the causative agent of cholera, has developed multi-drug resistance to many antimicrobial agents. In aquatic habitats, phages are known to influence the occurrence and dispersion of pathogenic V. cholerae. We isolated Vibrio phage VMJ710 from a community sewage water sample of Manimajra, Chandigarh, in 2015 during an outbreak of cholera. It lysed 46% of multidrug-resis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 58 publications
0
3
0
Order By: Relevance
“…Additionally, they demonstrated that when given 6–12 h before the bacterial challenge, the phage VMJ710 can prevent the progression of V. cholerae infection and ailment. This phage could be a good choice for oral delivery and could help treat cholera infections brought on by pathogenic multidrug‐resistant V. cholerae strains 205 . Another promising cure for cholera is probiotics.…”
Section: Management Antimicrobial Drug Resistance and Promising Chole...mentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, they demonstrated that when given 6–12 h before the bacterial challenge, the phage VMJ710 can prevent the progression of V. cholerae infection and ailment. This phage could be a good choice for oral delivery and could help treat cholera infections brought on by pathogenic multidrug‐resistant V. cholerae strains 205 . Another promising cure for cholera is probiotics.…”
Section: Management Antimicrobial Drug Resistance and Promising Chole...mentioning
confidence: 99%
“…This phage could be a good choice for oral delivery and could help treat cholera infections brought on by pathogenic multidrug‐resistant V. cholerae strains. 205 Another promising cure for cholera is probiotics. The goal of probiotic treatment for cholera infection is to bring back balance to the gut bacteria and stop V. cholerae strains from taking over the digestive system.…”
Section: Management Antimicrobial Drug Resistance and Promising Chole...mentioning
confidence: 99%
“…The EOP was calculated by dividing the average plaque-forming units (PFU) of the test bacteria by the average PFU of the host bacteria. Phages were categorized as high production (EOP ≥ 0.5) when the productive infection on the test bacteria resulted in at least 50% of the PFU found for the primary host; medium production (0.1 ≤ EOP < 0.5); low production efficiency (0.001 <EOP< 0.1); inefficient (EOP ≤ 0.001), and reference (EOP = 1) [33,34].…”
Section: Host Range Analysismentioning
confidence: 99%